Optimization of Biopori and Construction of Absorption Wells in Blawi Village to Overcome Annual Flood Disasters - Aini, Anisa Qurotul; Nabilah, Salwa; Umuronah, Umuronah (LPPPM STAI Darul Hikmah Bangkalan, 2024)
This activity was carried out in Blawi Village - Lamongan Regency. Floods often hit this village due to overflowing rivers and waterways due to high rainfall. In practice, infiltration wells for rainwater have never been implemented in Blawi Village, while biopores were only added at several points because this activity continued the previous year's activities. This community service activity made several rainwater infiltration wells and added biopores to accommodate the surface runoff water component from rainfall. This Student Organization Capacity Strengthening Program (PPK ORMAWA) activity was carried out by the Civil Student Association (HMS) of Lamongan Islamic University in collaboration with Blawi Village officials and residents for conservation-based waterlogging mitigation. Infiltration wells and biopores use a method that is very easy to implement, this activity is also useful for maintaining groundwater and utilizing biopore leaves for compost. This program can reduce the problem of inundation in Blawi Village during the rainy season